Beban Kerja dan Tantangan Profesional Guru Teknik SMK dalam Pembelajaran Praktik serta Implikasinya terhadap Mutu Pendidikan Vokasi: Kajian Literatur Sistematis - Wirawan, Monalisa; M. Ilham Shohibul Ulya; M. Reza Andreansyah Putra (Journal of Professional Education, 2026)
This study aims to analyze the workload and professional challenges of vocational high school engineering teachers in practical learning and their implications for the quality of vocational education. The study used a Systematic Literature Review method with the stages of identification, screening, feasibility evaluation, and thematic synthesis of relevant journal articles from the last ten years. Data sources were obtained from various accredited national journals and scientific publications that discuss vocational teacher professionalism, productive teacher workload, and practical learning in vocational high schools. The results of the study indicate that the workload of engineering teachers is multidimensional, including practical planning, facility and equipment management, occupational safety supervision, student skill evaluation, and increasing administrative demands. In addition, engineering teachers face professional challenges in the form of rapid industrial technology development, limited facilities, an unbalanced teacher-student ratio, and limited access to industrial training. These conditions have implications for the effectiveness of practical learning and variations in the quality of vocational high school graduates. This study concludes that improving the quality of vocational education requires proportional workload management, strengthening institutional support, and continuous professional development for engineering teachers. These findings provide a conceptual contribution in expanding the study of vocational education by positioning teacher working conditions as a strategic factor in improving the quality of practical learning.